A comparison of Northeast Atlantic killer whale (Orcinus orca) stereotyped call repertoires. Issue 1 (5th October 2020) - Selbmann, Anna; Deecke, Volker B.; Fedutin, Ivan D.; Filatova, Olga A.; Miller, Patrick J. O.; Svavarsson, Jörundur; Samarra, Filipa I. P.
Abstract: Killer whale call repertoires can provide information on social connections among groups and populations. Killer whales in Iceland and Norway exhibit similar ecology and behavior, are genetically related, and are presumed to have been in contact before the collapse of the Atlanto‐Scandian herring stock in the 1960s. However, photo‐identification suggests no recent movements between Iceland and Norway but regular movement between Iceland and Shetland. Acoustic recordings collected between 2005 and 2016 in Iceland, Norway, and Shetland were used to undertake a comprehensive comparison of call repertoires of Northeast Atlantic killer whales. Measurements of time and frequency parameters of calls from Iceland ( n = 4, 037) and Norway ( n = 1, 715) largely overlapped in distribution, and a discriminant function analysis had low correct classification rate. No call type matches were confirmed between Iceland and Norway or Shetland and Norway. Three call types matched between Iceland and Shetland. Therefore, this study suggests overall similarities in time and frequency parameters but some divergence in call type repertoires. This argues against presumed past contact between Icelandic and Norwegian killer whales and suggests that they may not have been one completely mixed population.